THE STRATAL WATER AS AN IMPORTANT ECONOMIC COMPONENT OF THE PRESENT DAY FOR OIL COMPANIES OF UKRAINE - Reva, M.; Chomko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The work determines the relevance of the study of stratal water as a hydromineral raw material, and what economic benefits it can bring to the oil company. This approach is important because it can reduce environmental pollution by stratal water. The authors theoretically justified the expediency of using stratal water as a hydromineral raw material for additional source of income. The inundation factor of the extracted fluid is defined as the main element, which reduces the company’s revenues in the process of oil production. This inundation factor can also determine an additional source of income when using stratal water as a hydromineral raw material. The article considers the content of chemical components and their concentrations as the main criterion, which makes it possible to consider stratal water as a hydromineral raw material. The article considers a theory that transfers stratal water from the expenditure component to the revenue component, and also graphically shows the profit that an oil company can obtain by selling hydromineral raw materials. Also, the paper gives information about rent fees in accordance with the tax code, which refers to the expenditure component, as well as the possibility of reducing it when using stratal water as a hydromineral raw material. The article identifies the main chemical components and their minimally cost-effective concentrations on the basis of which the stratal water is considered as valuable raw material. The article quotes the prices of international markets for these elements, which can be extracted from hydromineral raw materials. Using these indicators, the authors theoretically analyzed the Chutovsky and Kachanovskoye oil fields. This analysis showed what possible additional income an oil company can get.